Degradação de N- Hexadecano por consórcio de bactérias em microcosmos de sedimentos de manguezal - Falcão, Natália Maria Sousa (2014)
Mangroves are very susceptible to oil spills as a result of various human activities, including those on shore and off shore of oil industry. The need of cleaning methods is increasing to remedy such ecosystems, and techniques increasingly less harmful to the environment have been required, highlighting among them, the bioremediation. In this context, the aim of this study was to analyze the biodegradation of n-hexadecane, one of the derivatives of oil, in mangrove sediments by a consortium of bacteria previously isolated from a mangrove impacted by oil, for their application in bioremediation. To this, the bacterial strains were tested alone and in consortium. For the consortium, four microcosms were mounted which differed only in the source of carbon. The first contained only the organic matter inherent in the sediments, the second received glucose, the third were fed with n-hexadecane and glucose, and the last received only n-hexadecane. For the isolates, only the ability to degrade n-hexadecane was tested. The monitoring of biodegradation was done by counting the number of viable cells and determining the dehydrogenase activity. The results showed that both the metabolic activity and cell number were significantly higher in the microcosms which received an extra source of carbon, confirming the establishment and metabolism of the consortium in the sediments. Moreover, it was proved not to be necessary the addition of glucose, given that the consortium was able to grow only using n-hexadecane as a source of carbon and energy. From the analysis of the seven strains of the consortium alone, it was possible to infer that two strains HEX 5 and HEX 6, are essential for the consortium, since they are able to initiate the degradation of n-hexadecane, while HEX 1 and HEX 4 are also able to use n-hexadecane although need a longer adaptation phase. The remaining strains, HEX 2, HEX 3 and HEX 7 showed no significant metabolic activity in this experiment by the end of 25 days of monitoring. The consortium formed by HEX 1, HEX 4, HEX 5 and HEX 6, comprising respectively strains of the genera Sphingomonas, Micrococcus, Gordonia e Micrococcus, is a potential product for bioremediation of hexadecane-contaminated mangrove sediments by the strategy of bioaugmentation.